2018
DOI: 10.1007/s11060-018-2993-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic features of spinal meningioma: a thorough analysis from a single neurosurgical center

Abstract: Our analysis of the largest SM cohort in scale from a single institution offers a comprehensive view of the clinical characteristics of surgically treated SM, revealing the distinct biology of SM in comparison to its cranial counterparts, and providing guidance to improve surgical management of SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 26 publications
4
48
0
3
Order By: Relevance
“…The recurrence status cannot be completely predicted by histopathologic grade alone, as it is mainly based on histopathological characterizations of mitotic rate, cellular features of atypia, and local invasion (18). Meningiomas are well-known for their female-biased predominance (19), but tumors in male patients demonstrate not only a higher annual growth rate (20) but also a higher probability of recurrence (21)(22)(23). Previous studies have proposed molecular markers for prognostic scoring systems in recent years (14,21,(24)(25)(26), and a better WHO classification of meningiomas integrated with independent molecular markers may help to predict the recurrence risk and adjust treatment plans for patients with meningiomas.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence status cannot be completely predicted by histopathologic grade alone, as it is mainly based on histopathological characterizations of mitotic rate, cellular features of atypia, and local invasion (18). Meningiomas are well-known for their female-biased predominance (19), but tumors in male patients demonstrate not only a higher annual growth rate (20) but also a higher probability of recurrence (21)(22)(23). Previous studies have proposed molecular markers for prognostic scoring systems in recent years (14,21,(24)(25)(26), and a better WHO classification of meningiomas integrated with independent molecular markers may help to predict the recurrence risk and adjust treatment plans for patients with meningiomas.…”
Section: Introductionmentioning
confidence: 99%
“…An initial review of the literature describing several large surgical studies of sporadic meningiomas (NF2-associated tumor studies are more rare and usually underpowered) indicated that the mean age at surgery for sporadic cranial meningiomas was between 53.8 and 58.3 y.o. [14][15][16][17] and the mean age at surgery for sporadic spinal meningiomas was between 53.0 and 69.0 y.o. [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] and the mean age at surgery for sporadic spinal meningiomas was between 53.0 and 69.0 y.o. [17][18][19][20][21] . In one study, in which both cranial (N = 9,806) and spinal (N = 483) tumors were operated on at the same Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…На менингиомы спинного мозга приходится от 25% до 46% от всех первичных экстрамедуллярных спинальных опухолей и от 7% до 12,7% от всех менингиом центральной нервной системы. Заболевание в 0,34-2,5 раза чаще проявляется у женщин, чем у мужчин, притом в 85-90% случаев -в возрасте 50-70 лет [2,4,5]. Изучение эпидемиологии спинальных опухолей в Канаде показало, что до 30,7% всех интрадуральных опухолей спинного мозга составляют менингиомы.…”
unclassified
“…Тотальное удаление таких опухолей, в подавляющей своей массе носящих доброкачественный характер, приводит в большинстве случаев к выздоровлению больных, но нередко -в 4-31% случаев -они рецидивируют вновь, что значительно ухудшает качество жизни оперированных [5,8,9]. Столь высокие цифры рецидивирования спинальных менингиом и значительный статистический разброс в появлении случаев рецидивов связаны, в первую очередь, с субъективизмом при определении степени радикальности выполненных оперативных вмешательств.…”
unclassified